BUILDING CUSTOMER LOYALTY FOR USERS OF KENCANA TRUSS LIGHT STEEL PRODUCTS IN BALI PROVINCE - I Putu Yoga Adi Pratama; Ida Bagus Raka Suardana (RADJA PUBLIKA, 2026)
Customer loyalty has become a critical factor in maintaining competitiveness within Indonesia's lightweight steel industry, particularly in regions experiencing rapid construction growth such as Bali Province. This study aims to analyze the influence of product quality, brand image, and trust on customer loyalty, with customer satisfaction serving as a mediating variable among users of Kencana Truss lightweight steel products in Bali. A quantitative research approach with a causal associative design was employed. Data were collected through questionnaires distributed to 240 respondents selected using purposive sampling, consisting of retail customers, contractors, and building material retailers who had used Kencana Truss products. The data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The findings reveal that product quality has a positive and significant effect on brand image, customer satisfaction, and trust. Furthermore, brand image and trust significantly enhance customer satisfaction, while customer satisfaction exerts a strong positive influence on customer loyalty. The mediation analysis also confirms that customer satisfaction significantly mediates the relationship between product quality and customer loyalty. These results indicate that maintaining consistent product quality not only strengthens brand image and customer trust but also enhances customer satisfaction, ultimately fostering long-term customer loyalty. The study contributes to relationship marketing literature by providing empirical evidence from the Indonesian lightweight steel industry and offers practical implications for manufacturers seeking to improve customer retention through quality management and customer satisfaction strategies.